Analysis of diarrhea cases based on weather elements in Yogyakarta City 2017-2021 - Ramadhanti, Inas Tri; Kusnanto, Hari; Ramadona, Aditya Lia (BKM Public Health and Community Medicine, 2025)
Purpose: The objective of this study is to determine the relationship between weather elements (such as rainfall, temperature, humidity, and sunshine duration) with cases of diarrhea, as well as to map the areas vulnerable to diarrhea in Yogyakarta City using data from 2017 to 2021. Methods: This study used an ecological study design with Graphical/Time Trend Analysis, correlations, non-linear analysis using the Generalized Additive Model (GAM), and spatial analysis. Results: Statistically, temperature lag of 0 - 3 months has a negative correlation (p-value < 0.05; rlag1= -0.672), and humidity lag of 0 - 3 months has a positive correlation (p-value < 0.05; rlag1= 0.414) with diarrhea. Severe cases of diarrhea, even during the COVID-19 pandemic, are still being brought to health services, suggesting a serious underlying cause, such as rotavirus infection. Further multivariate analysis showed that the most dominant weather element related to diarrhea was temperature lag for 3 months, with an R-squared value of 0.516. Diarrhea is distributed across sub-districts in Yogyakarta City, but there are six sub-districts with high vulnerability to diarrhea: Danurejan, Pakualaman, Jetis, Kotagede, Gedongtengen, and Gondomanan. Conclusions: The most dominant weather element related to diarrhea in Yogyakarta city is the temperature from the previous three months (lag 3). Danurejan, Pakualaman, Jetis, Kotagede, Gedongtengen, and Gondomanan sub-districts have high vulnerability to diarrhea.